Oilfield chemistry and its environmental impact - Craddock, Henry A., 1956- (John Wiley & Sons Ltd, 2018)
Consolidates the many different chemistries being employed to provide environmentally acceptable products through the upstream oil and gas industry.-- Provided by publisher.
Keywords: Petroleum engineering.; Petroleum chemicals.; Gas engineering.; Green chemistry.; Environmental protection.; Demulsification.; Oil well drilling -- Environmental aspects.; Drilling muds.; Oil field brines -- Environmental aspects.; elektronické knihy; electronic books